Answer:
[tex]x = \dfrac{11}{2} \textsf{ or } 5 \dfrac{1}{2} \textsf{ or } 5.5[/tex]
Step-by-step explanation:
To solve the equation [tex]\ln(x - 3) - \ln(x - 5) = \ln 5[/tex] using properties of logarithms, we can utilize the quotient rule of logarithms, which states:
[tex] \ln \left(\dfrac{a}{b}\right) = \ln a - \ln b [/tex]
Given:
[tex] \ln(x - 3) - \ln(x - 5) = \ln 5 [/tex]
We can combine the logarithms on the left-hand side using the quotient rule:
[tex] \ln \left(\dfrac{x - 3}{x - 5}\right) = \ln 5 [/tex]
Now, according to the properties of logarithms, if [tex]\ln u = \ln v[/tex], then [tex]u = v[/tex]. Thus, we have:
[tex] \dfrac{x - 3}{x - 5} = 5 [/tex]
Now, solve this equation for [tex]x[/tex]:
[tex] x - 3 = 5(x - 5) [/tex]
[tex] x - 3 = 5x - 25 [/tex]
Now, solve for [tex]x[/tex]:
[tex] 25 - 3 = 5x - x [/tex]
[tex] 22 = 4x [/tex]
[tex] x = \dfrac{22}{4} [/tex]
[tex] x = \dfrac{11}{2} [/tex]
So, the solution to the equation is:
[tex]x = \dfrac{11}{2}[/tex]